EFFECT OF ISOMETRIC SQUAT EXERCISE ON SPRINT PERFORMANCE OF FOOTBALL PLAYERS - Basit Ali; Syed Muhammad Bilal Gillani; Muhammad Zeeshan Butt (The Sky)
A soccer match makes heavy demands on both aerobic and anaerobic metabolism. Elite players run 8–12 km during a game. Nevertheless, anaerobic metabolism is also crucial in sprints, jumps, and tackles. Many studies have stated that aerobic and anaerobic strength are significant features in soccer games. During a soccer match, soccer team members performed 60 to 70 runs from 12 to 15 m. Sprint running success, with or without the ball, is therefore a significant factor that can explain a winning team's supremacy. In essential ball duals, sprint could be key. In certain cases, the player should be quicker and more effective than the opponent to score goals or to avoid goals being scored. In addition, acceleration and speed can enhance skills vital to soccer, such as turning, sprinting, and changing tempo, by improving strength in appropriate muscles or muscle groups. The study was to evaluate the effect of isometric squat exercise on sprint performance of football players. The sample of 60 student were selected from the population of University of Lahore football team. Within 3 to 5 days after base training pre-test will be conducted in the morning by using 40-yard dash test. Post-test will be conducted after completion of Isometric Squat exercise training sessions. The results show that, differences between the two test 40 Yard Dash Test Post-Test of Experimental Group and 40 Yard Dash Test Post-Test of Control Group. This research study discovered that there was a statistically significant improvement in sprint performance by using Isometric Squat exercise Program.